Reflection seismic studies over the end-glacial Burträsk fault, Skellefteå, Sweden - Juhlin, Christopher; Lund, B. (2011)
Reflection seismic data were acquired along a ca. 22 km long profile over the end-glacial Burträsk fault with a nominal receiver and source spacing of 20 m. A steeply dipping reflection can be correlated to the Burträsk fault, indicating that the fault dips at about 55° to the southeast near the surface. The reflection from the fault is rather poorly imaged, probably due to a lateral offset in the fault of about 1km at this location and the crookedness of the seismic profile in the vicinity of the fault. A more pronounced steeply dipping reflection is observed about 4km southeast of the Burträsk fault. Based on its correlation with a topographic low at the surface this reflection is interpreted to originate from a fracture zone. There are no signs of large displacements along this zone as the glacial ice receded, but earthquakes could be associated with it today. Other reflections on the processed seismic section may originate from changes in lithological variations in the supra-crustal rocks or from intrusions of more mafic rock. Constraints on the fault geometry provided by the reflection seismic data will help determine what stresses were required to activate the fault when the major rupture along it occurred ca. 9500 years ago. © Author(s) 2011.